2021
DOI: 10.3389/fphar.2021.714584
|View full text |Cite
|
Sign up to set email alerts
|

Modified Huangqi Chifeng Decoction Attenuates Proteinuria by Reducing Podocyte Injury in a Rat Model of Immunoglobulin a Nephropathy

Abstract: Modified Huangqi Chifeng decoction (MHCD) has been used to reduce proteinuria in immunoglobulin A nephropathy (IgAN) for many years. Previously, we have demonstrated its protective role in glomerular mesangial cells. Podocyte injury, another key factor associated with proteinuria in IgAN, has also attracted increasing attention. However, whether MHCD can reduce proteinuria by protecting podocytes remains unclear. The present study aimed to investigate the protective effects of MHCD against podocyte injury in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…As aforementioned, podocyte injury is a key factor associated with proteinuria in IgAN ( 5 ), in which inflammation-induced podocyte injury serves an important role ( 42 ). To establish an in vitro podocyte injury model, the specific LPS concentration able to induce podocyte injury was determined with a CCK-8 assay before sampling and testing.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As aforementioned, podocyte injury is a key factor associated with proteinuria in IgAN ( 5 ), in which inflammation-induced podocyte injury serves an important role ( 42 ). To establish an in vitro podocyte injury model, the specific LPS concentration able to induce podocyte injury was determined with a CCK-8 assay before sampling and testing.…”
Section: Discussionmentioning
confidence: 99%
“…IgAN patients will develop proteinuria, which will continue to worsen. Podocyte injury under inflammatory stress is a key factor associated with proteinuria in IgAN patients ( 5 ). Based on a microarray dataset GSE83233, the TNF-α pathway was identified as an important signal when Bud exerts its anti-inflammatory effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Shenkang injection contains dahuang ( Radix et Rhizoma Rhei ), danshen ( Radix Salviae Miltiorrhiae ), honghua ( Flos Carthami ), and huangqi ( Radix Astragali ). Modern studies have found that dahuang ( Radix et Rhizoma Rhei ) can improve kidney function and improve pathological kidney damage, [ 23 ] reduce the LPS-induced inflammatory macrophage response, [ 24 ] reduce renal fibrosis and delay renal failure [ 25 ] ; huangqi ( Radix Astragali ) can protect glomerular mesangial cells and reduce proteinuria, [ 26 ] promote water and sodium excretion, and protect the kidney [ 27 ] ; danshen ( Radix Salviae Miltiorrhiae ) has anti-inflammatory, anticoagulant, and antioxidant properties [ 28 ] and anti-anemia effect, [ 29 ] can effectively improve the microcirculation in CRF patients.…”
Section: Discussionmentioning
confidence: 99%